SMALL GUT ATRESIA IN NEONATES - Kamal, Arshad; Khan, Kifayat; Rahman, Inayat ur; Khan, Ayub (Journal of Ayub Medical College Abbottabad, 2010)
Background: Small gut atresia is a common neonatal surgical problem. Early diagnosis and timely management of the neonate can reduce mortality and morbidity in these patients. The aim of this study was to note the causes of mortality and morbidity in these neonates. Methods: This was a prospective study conducted at Lady Reading Hospital (LRH) Peshawar from August 2007 to August 2009. All patients with small gut atresia were included in this study. Neonates having intestinal obstruction due to another cause were excluded from this study. The diagnosis of small gut atresia was usually established peroperatively as other causes of intestinal obstruction like meconium ileus or meconium plug syndrome etc. in neonatal period mimic small gut atresia. Results: A total of 40 neonates with small gut Atresia were included in this study. Among them 28 were males and 12 were females. Age of presentation ranged from 1 to 8 days. Weight of the neonates ranged from 1.8-2.8 Kg with the mean weight of 2.43 Kg. Peroperatively type-III(a) Atresia was the commonest type 20 (50%). Resection and end to end anastomosis was done in 31 cases. Nine neonates needed ileostomy. Financial constraints, late presentation, aspiration, sepsis, gut perforation and gangrene were the main contributors to death of these neonates. Conclusion: Neonates having small gut atresia should be treated at a centre equipped for dealing neonates during all stages of management. Keywords: Small gut atresia, Management, Neonate